Screening for Coronavirus Disease 2019 (COVID-19) at the Pediatric Emergency Department During Different Pandemic Phases - Stacevičienė, Indrė; Burokienė, Sigita; Steponavičienė, Aušra; Vaičiūnienė, Daiva; Puronaitė, Roma; Jankauskienė, Augustina (Frontiers in Pediatrics, 2021)
The wide spectrum of COVID-19 symptoms complicates the selection of target groups for screening. We aimed to compare data of children screened for COVID-19 at the pediatric emergency department in Vilnius between different phases throughout one year (Phase I: March–May, 2020; Phase II: June–September, 2020; and Phase III: October, 2020 – February, 2021) and to evaluate the possible predictors of the disease. SARS-CoV-2 PCR tests were positive for 2.7% of tested children (248/9238), significantly higher during the Phase III (5.5%) compared with the Phase I (0.6%, p=0.000) and Phase II (0.3%, p=0.000). Infants and teenagers (12-17 years) accounted for a larger proportion of COVID-19 patients (24.6% and 26.2%, respectively) compared to other age groups: 1-2 years (18.9%), 3-6 years (14.9%) and 7-11 years (15.3%). There were more COVID-19 cases among children with a known SARS-CoV-2 exposure compared to those who did not declare any contact (18.2% vs 1.1%, p=0000). When symptoms were adjusted for age, gender and known exposure to SARS-CoV-2, we found that fever (OR 2.66; 95% CI 1.89-3.81), pharyngitis (OR 1.35; 95% CI 1.01-1.80), headache (OR 1.81; 95% CI 1.09-2.90), and anosmia/ageusia (OR 6.47; 95% CI 1.61-22.47) were the most significant predictors. Conclusion: Although high numbers of testing were maintained throughout the year, the positive test results were significantly higher during the Phase III. Age (<1 year, 12-17 years), a history of exposure to SARS-CoV-2 and some symptoms, such as fever, pharyngitis, headache and anosmia/ageusia could aid in targeting groups for screening for COVID-19 in children.